Middelalderlige kirkelader i Danmark - Bjerregaard, Mikael Manøe (Kuml, 2003)
Medieval Church Barns in Denmark The subject of this article is medieval church barns within the area of present-day Denmark. A church barn (or tithe barn) is a building erected near a parish church and used for storing the crops that local peasants paid as tithes or taxes to the church. Constructed as functional buildings for the church, these barns have both a clerical and a secular context. In 1912 M. Mackeprang gave an account of relevant written sources and made a provisional list of barns preserved at that time. In this work the list has been revised to describe the present day situation and it is established that there are 31 church barns preserved today. There are a few additional buildings of which the original function is uncertain that could be added to this list (fig. 1). Since Mackeprang’s article no total account of Danish church barns has been compiled, and relevant information therefore had to be sought from various sources. The most important written sources for medieval and post-medieval times are the letters from the Chancellery (Kancelliets brevbøger) and church laws from the early Protestant period. Although these documents are not medieval, in this article they are used to give a probable picture of the condition of the medieval church barns. Another important source is the notebook that the Funen bishop Jacob Madsen made during his visitation of every parish in his diocese in the late 16th century. The bishop often mentions the condition of church barns and sometime adds some more information. His work is very reliable and gives an idea of the status of the Funen church barns approximately 50 years after the Reformation. All of the preserved barns are situated in the churchyard of the church to which they belong. Some are built at the periphery of the churchyard so that one of the walls forms part of the churchyard wall. Some church barns are free-standing within the churchyard (fig. 2), while a few are built as an extension of the actual church. This is the case of the preserved church barn in Voldum (fig. 3) and also of the now lost barn in Brønshøj. Jacob Madsen’s notes tell us that if the church was situated far from the village the church barn could be placed centrally in the village instead. All of the preserved church barns are made of stone. On Zealand they are mainly built of bricks but on the southern part of the island local limestone is also used to a great extent. (fig. 11). On Funen barns are built with both bricks and granite boulders (fig. 4). The few preserved barns in Jutland have plinths of granite boulders while the walls are built of brick. The fact that church barns are brick-built is surprising because secular barns in medieval Denmark were always wooden constructions. Perhaps many of the lost church barns were timbered or half-timbered buildings. This was certainly the case of some of the Funen barns which Jacob Madsen described. This can also be deduced from a document from the year 1573 in which a special licence was given to tear down all church barns in the Århus diocese that were not brick-built. This suggests that the remaining brick-built church barns may not be representative of the majority of the medieval barns. Judging from the remaining barns and reliable measurements from ruined barns the dimensions of these buildings are typically 14-16 m x 7-9 m. The biggest barn is that in Tranebjerg on the island of Samsø (21.5 m x 9 m) while the barn in Mogenstrup, no longer in existence, was only 8.5 m by 4.23 m. Thus the dimensions of the medieval barns seem to have varied greatly. Some of the existing barns have been reduced (Melby, fig. 10) or expanded (Mesinge, fig. 5) in size. It is difficult to determine what was used for roofing the medieval barns. It is unlikely, however, that a barn with a stepped gable would also have a thatched roof, since such a roof would not fit tight against the gable but would have to overlap the top of it. The decorated gables of some of the barns are described in detail because these decorations can be used to date the barns (figs. 10-12). Caution has to be exercised, however, since these gables have often been restored freely, as for example in Strø (figs. 6 & 7). The church barn in Skårup has also been restored, but the reconstructed form of the gables is based on traces in the brickwork (figs. 8 & 9). In general the decorated gables of church barns seem to adopt local types of decoration that are also used in the churches. An example is the lost church barn in Ejby (fig. 20). It is not known whether church barns have existed in Denmark since the tithe regulations were introduced in the 12th century or if they are solely a late medieval phenomenon. Palle Lauring argues that Finderup Barn, in which King Erik Klipping was killed in 1289, was the village church barn. If this is true this would be the earliest mention of a Danish church barn. In Hjallese, Funen, remains of foundations have been interpreted as a church barn. This building is dated by two coins from the reign of Christoffer II (1320-1326). If this is correct it would be the oldest archaeologically dated church barn in Denmark. All of the preserved church barns are much later. These buildings date from 1450-1550, to judge from the decorated gables. The barn in Øster Egesborg is the only one to have been dendrochronologically dated. The trees used for its rafters were felled in approximately 1485-90. Even though church barns generally seem to be a medieval phenomenon it is apparent from written sources that church barns were also built in the second half of the 16th century and even as late as the beginning of the 17th century. However, in the attempt to make an account of the distribution of church barns in medieval Denmark it is often impossible to differentiate between barns built before 1536 and those built after. All references to church barns that could be found were therefore included for the purposes of the map (fig. 13). The main source of information about lost church barns on Zealand is Danmarks kirker, a series of descriptions of the Danish churches which now covers all of Zealand. Jacob Madsen is the main source for Funen , while information about church barns in Jutland is much more scarce and diffusely spread. The map of Jutland may not at the moment, therefore, give as true a picture of the medieval situation as the maps of Zealand and Funen. It is often claimed that church barns were a phenomenon concentrated in the eastern parts of Denmark (Zealand, Funen and Eastern Jutland) and generally this work supports this assumption. However, there have been church barns even in the northwest part of Jutland. On the other hand only one church barn is mentioned in the sources for the southern part of Jutland. In a church law from 1537 it is said that in every parish peasants should bring their crops to the church barns, but as the above shows there might not have been a church barn in every parish throughout the country. Possible explanations for the relatively few church barns in Jutland will be given later. Church barns also existed in the boroughs (fig. 15). The function of these buildings was to house the crops that came from the town’s fields, which were cultivated by the citizens. Furthermore the churches in the boroughs could function as parish churches for peasants in nearby villages. In theory tithe should be paid on all agricultural products, but in Denmark the crop tithe was by far the most important. In other European countries the tithe was divided into four portions: the vicar’s tithe, the bishop’s tithe, the tithe to keep the church well-maintained and equipped (the so-called fabrica), and finally one fourth of the tithe was given to the poor. In Denmark the tithe was only divided into three portions – leaving nothing to the poor. Even inside the Danish kingdom the practice of tithe varied greatly. A bishop’s tithe was introduced on Zealand, in Scania and in Slesvig in the late 12th century, but in the rest of Jutland and on Funen the bishop was paid a fixed amount of money (the “bishop’s gift”) that would often be much less than a third of the tithe. The dislike of the bishop’s tithe could among other things stem from the fact that this tithe should in theory be transported to the bishop’s town, which could be very far from the village. When the bishop’s tithe was introduced by law on Zealand is it said in the letter of the law that the tithe should only be brought to a place within the parish – probably to ease the acceptance of this new tax. Only in 1443 was the bishop’s tithe introduced in Jutland and on Funen, and it was much disliked. Which of the three parts of the tithe was stored in the church barns? In King Christian III’s church law from 1536 it is mentioned that the tithe should be brought to the church barn and then divided in three. On the other hand it is reasonable to assume that the vicar’s third of the tithe was brought directly to the vicarage, which was situated within the parish. One source indirectly points at this fact. In 1536 it is said that the peasants should be given two barrels of beer on the day they bring the tithe – and it is then added that this beer should not be consumed at the vicarage, as had often happened before. Maybe this is the reason a late 16th century barn beside the vicarage of Nimtofte in Eastern Jutland is called the church barn. So, did the church barns house the bishop’s tithe, the fabrica or both? As a result of the Reformation in 1536 the church’s property was confiscated by the king. The king now became head of the church and the bishop’s tithe was now called the king’s tithe. Apparently in the first years after the Reformation this change was only in name and therefore the practices concerning the king’s tithe in the early Protestant period probably reflect how the bishop’s tithe was handled in the late medieval period. In 1546 it is said in a letter from the Chancellery that the vicar and the churchwarden were responsible for hiring two men to thresh the tithe and then divide it into two parts: the fabrica and the king’s tithe (fig. 17). In a letter from 1542 it is said that the Scanian peasants were to bring one third of the tithe (the king’s tithe) to the church barn. In the Middle Ages the churchwardens were responsible for the fabrica and probably also for the church barns. The church barn in Vedtofte, Funen, was built by the churchwardens in 1554 using the fabrica. Jacob Madsen suggested in 1589 that the church barn in Turup, Funen, could be used as a house for the vicar, but the churchwarden had the final word, which was no. It is thus plausible that the fabrica was stored in the church barns, but of course this crop might also have been brought to the farm of one of the churchwardens who lived in the parish. It is most likely that the bishop’s tithe was stored in the church barn until it could be picked up by the bishop’s men. Some twenty years after the Reformation new rules were introduced that the peasants were to bring the king’s tithe (formerly the bishop’s tithe) to the respective castles and not just to the churchyard as previously. In 1577 a general law for Zealand was made that the peasants should bring the tithe in sheaves to whoever owned it. It was no longer enough to bring it to the churchyard. The conclusion is that the vicar’s tithe was probably brought to the vicarage, the fabrica could be stored in the church barn or at the churchwarden’s house and the bishop’s tithe was most likely always stored in the church barn. A few of the largest church barns may have been drive-through buildings, meaning that wagons entered through a gate in one end of the building, the sheaves were unloaded inside the building, and the wagon left via a gate at the opposite end of the building. The church barn in Kalundborg (fig. 18) and possibly also that in Tranebjerg had this function. In the smaller barns the sheaves were simply carried into the barn (fig. 16) or passed in through a hole in the wall. The interiors of the barns have been radically changed everywhere but some have been archaeologically examined. The church barn in Flemløse had been divided into three rooms, one of which seems to have had a cellar. The finding of charcoal in Skårup church barn suggests that the building was also used for purposes other than storage. In Skårup there were also remains of a hard clay floor that would have been ideal for threshing. Since we know nothing about church barns until the last century of the Middle Ages it has been claimed that originally the church lofts were used to store the crops. When vaults were introduced in many parish churches in late medieval times, leaving no storage room in the lofts, it became necessary to build church barns. This could explain the few church barns in Jutland since many churches in that part of the country never had vaults built on. From post-medieval times we know that in several churches in Southern and Northern Jutland the lofts were used for storing crops. In Egen church a winch used for this purpose still exists and one can suppose that this also reflects the medieval practice (fig. 19). However, this poses the question of where the threshing would then have taken place, because it seems that the tithe was normally handed over in sheaves and not in the form of grain. Furthermore there does not seem to be a clear connection between vaults and church barns. All of the vault-less churches mentioned by Jacob Madsen also had church barns. Probably the church barns must be considered as part of the massive construction works that were undertaken in connection with the Danish churches in the last 150 years of the Middle Ages. Vaults, towers, porches, etc. were built. This building activity was most intensive in the eastern part of the country, while the western part of Jutland tended to follow at a much slower pace, and in the year 1536 the Reformation put an abrupt end to it all. Another reason for the lack of church barns in many parts of Jutland could be that they were wooden constructions. Most of the church barns we know about are mentioned in the sources when they are torn down and the bricks or boulders sold. Wooden constructions are less valuable in this sense and might be underrepresented in the written sources for this reason. Immediately after the Reformation the use of the church barns probably did not change dramatically. But in the late 16th century more church barns fell out of use. This was encouraged by law in 1643. As more and more churches became private property the landlord owned both church buildings and tithe. For the church owner it was more convenient to have the tithe brought directly to his own barn and as the church barns lost their original function the materials of which they were built could be used for restoring the churches – another matter for which the church owner was responsible. Many church barns were lost on this account in the 1660s. The few church barns that remain today survived because they were used for a new purpose soon after the Reformation. In the boroughs they were often used as schools (fig. 14) and in the country parishes they could be converted into workhouses for poor people (fig. 21). The church barns have not drawn as much attention to themselves as an object of research as have the medieval churches, but they are a unique group of medieval buildings and together with the churches they form a unity that dates back almost 500 years. Mikael Manøe Bjerregaard Afdeling for Middelalderarkæologi Aarhus Universitet Moesgård